Exchange Rate Volatility and Economic Growth: Managed Floating and Free-Floating Regime - Utomo, Felicia Grace Ratnasari; Saadah, Siti (University of Merdeka Malang, 2022)
Indonesia's economy has been in its worst period. At that time, economic growth was below zero percent. One of the reasons is the high volatility of exchange rates in 1997-1998 when the exchange rate regime was transferred from managed floating to free-floating. Now, the high volatility of the exchange rate is feared to have an impact on the economy, especially economic growth, because it is one of the main focuses of the government's current achievements. Therefore, this study aims to see whether volatility impacts Indonesia's economic growth, especially in two different exchange rate regimes, managed floating and free-floating. This empirical research is based on quarterly data for 1994 - 2020, using the estimation method of Generalized Autoregressive Conditional Heteroskedasticity (GARCH) and Vector Autoregressive Model (VAR). The result shows that exchange rate volatility has a significant negative effect on economic growth, while the exchange rate regime moderates the impact of exchange rate volatility on economic growth.